Synthetic Modifications of the Linkage Region of Proteoglycans and Impact on CSGalNAcT‐1. Issue 2 (14th January 2022) - Ayela, Benjamin; Heis, Floriane; Poisson, Thomas; Pannecoucke, Xavier; Fournel‐Gigleux, Sylvie; Gulberti, Sandrine; Lopin‐Bon, Chrystel
Abstract: We herein report for the first time a multi‐step synthesis of a library of disaccharides and trisaccharides of the linkage region of proteoglycans (PGs) having a d ‐galactose modified at position C‐2, C‐4 or C‐6 by replacing the hydroxyl group by methoxy or deoxy moieties. Efficient radical dehalogenation, Barton‐McCombie reaction, O ‐methylation and stereoselective glycosylation are described. We also report preliminary results of the effect of these modifications upon the activity of recombinant chondroitin sulfate N ‐acetylgalactosaminyltransferase‐1 (CSGalNAcT‐1), an enzyme involved at the bifurcation step of the biosynthesis of PGs. Abstract : Multi‐step synthesis of a library of variously modified disaccharides and trisaccharides of the linkage region of proteoglycans (PGs) having a d ‐galactose modified at position C‐2, C‐4 or C‐6 position by replacing the hydroxyl group by methoxy or deoxy moieties is described. Preliminary results of the impact of these modifications upon CSGalNAcT‐1 are also reported.